Advances and Challenges in Space-time Modelling of Natural Events - Porcu, Emilio; Montero, José-María; Schlather, Martin (Lecture Notes in Statistics - Proceedings ;, 2012)
This book arises as the natural continuation of the International Spring School "Advances and Challenges in Space-Time modelling of Natural Events," which took place in Toledo (Spain) in March 2010. This Spring School above all focused on young researchers (Master students, PhD students and post-doctoral researchers) in academics, extra-university research and the industry who are interested in learning about recent developments, new methods and applications in spatial statistics and related areas, and in exchanging ideas and findings with colleagues.